The Keynesian multiplier effect reconsidered - Yoshiyasu Ono (Osaka University, Institute of Social and Economic Research (ISER), 2009)
The Keynesian multiplier effect is reinterpreted and several issues that may have misled assessments of the effect of fiscal spending are discussed. It is shown that even in the textbook Keynesian framework some transfer policy 'reduces' aggregate demand and that public works spending may completely crowd out private consumption. Useless public works are found to be equivalent to transfers although they increase accounting national income more than transfers do. The net effect of fiscal spending on national benefits is explored and shown to equal only the direct benefit created by the spending.
Keywords: E12; E62; E01; 330; the multiplier effect; public works; unemployment benefits; national income accounting; Multiplikator; Keynesianismus; Öffentlicher Bauauftrag; Öffentliche Sozialleistungen; Theorie